Boron in Human Nutrition and its Regulations Use - Dinca, Laura; Scorei, Romulus (Journal of Nutritional Therapeutics, 2013)
According to the literature, there are increasingly more scientific data regarding the boron importance in the human nutrition. The request for boron supplements has become more significant due to the following two discoveries: boron transport within the animal cell and the cellular signaling of some bacteria by a sugar borate complex. It is necessary to establish the benefits and the toxicity of boron consumption for humans and animals, although a biological function of boron has not been defined yet. In addition, it is important to know the legal regulations for boron use worldwide, its physiological effects and health uses.